Relationship between Individual Characteristics and Hearing Complaints in Home Industry Workers - Herlambang Yahya Yudhistira; Ahmad Rido'i Yuda Prayogi; Amalia Layina Ulfa; Llilis Sulistyorini; Ayik Mirayanti Mandagi (Universitas Airlangga, 2022)
Introduction: Home metal industry is an informal industry activity engaged in the manufacture of metal. The process of metal-making crates noise that causes hearing loss complaints in workers. The purpose of this study was to analyze the relationship between workers’ individual characteristics and hearing complaints in metal-making home industry workers in Ngingas North Village, Sidoarjo Regency. Methods: This research used an analytic observational method with a cross sectional design. The population was 28 workers, and the research samples were 23 workers in the metal cutting and welding areas, determined using a purposive sampling technique referring to the inclusion criteria. The independent variables used in this study was individual characteristics including age, years of work, and the utilization of ear protection. The dependent variable in this study was hearing complaint and the data analysis used contingency coefficient C method. Results: Most workers were aged 26-45 years at 65.2%, had years of service >15 years at 43.5%, did not use ear protection at 69.6%, and complained of hearing loss at 65.2%. The results of the contingency coefficient C test analysis obtained a p-value <0.05 between individual characteristics and hearing complaints. Conclusion: There was a relationship between individual characteristics including age, years of service, and use of ear protection and hearing complaints.Keywords: ear protection, age, hearing complaints, years of work